2005
DOI: 10.4049/jimmunol.175.2.820
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell-Mediated Cross-Presentation of Antigens Derived from Colon Carcinoma Cells Exposed to a Highly Cytotoxic Multidrug Regimen with Gemcitabine, Oxaliplatin, 5-Fluorouracil, and Leucovorin, Elicits a Powerful Human Antigen-Specific CTL Response with Antitumor Activity in Vitro

Abstract: Gemcitabine, oxaliplatin, leucovorin, and 5-fluorouracil (GOLF) is a novel multidrug regimen inducing high levels of necrosis and apoptosis in colon carcinoma cells. This regimen is also able to promote a process of Ag remodeling including up-regulation of immunotherapy targets like carcinoembryonic Ag (CEA), thymidylate synthase (TS). We have conducted a preclinical study aimed to investigate whether these drug-induced modifications would also enhance colon cancer cell immunogenicity. Several CTL lines were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 42 publications
2
58
0
Order By: Relevance
“…T cells [44][45][46]. As has been noted in the literature, many chemotherapeutic agents have been shown to slightly increase the anti-tumor immune response via the cross-presentation of an apoptotic tumor body, mediated by caspase activation [24,25,[47][48][49][50]. On the basis of this observation, we believe that CH-CTX ?…”
Section: Discussionsupporting
confidence: 63%
“…T cells [44][45][46]. As has been noted in the literature, many chemotherapeutic agents have been shown to slightly increase the anti-tumor immune response via the cross-presentation of an apoptotic tumor body, mediated by caspase activation [24,25,[47][48][49][50]. On the basis of this observation, we believe that CH-CTX ?…”
Section: Discussionsupporting
confidence: 63%
“…This phase Ib trial evaluated the safety and biological activity of TSPP administered alone or in combination with an immune-adjuvant regimen (IG-1) containing granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-2 [15], in advanced cancer patients. The rationale to combine TSPP with IG-1 regimen derived from preclinical in vitro findings [12,14,16,17] and previous clinical studies, where the IG-1 regimen alone [15] or in combination with 5′FU-based chemotherapy was found to be safe, able to generate activated dendritic cells (DCs) and to promote an efficient antigen-specific T cell response [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…We already demonstrated that tumor cell exposure to GOLF regimen increases the expression of multiple TAA (like TS, CEA, and EGFR), enhances the expression of danger signals and "eat-me" molecules, and induces immunogenicity in colon and breast cancer cell models in vitro. 9,13,14,[16][17][18][19] These preclinical findings provided a clear rationale to investigate the GOLF regimen in combination with an immune-adjuvant IG-1 cytokine regimen (sc. Interleukin (IL)-2 and sc.…”
Section: Introductionmentioning
confidence: 99%